The Narasi Visual dan Konstruksi Makna Rumah pada Short Movie dari lagu Kita Usahakan Rumah itu Karya Sal Priadi - RESTIA, NOVI; Hubbah, Zahratul; Reyzakhalis, Mohd (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2026)
This study aims to analyze visual narratives and the construction of “home” meaning in the short movie “Kita Usahakan Rumah Itu” by Sal Priadi. This research is motivated by the growing production of music-based audiovisual works that convey complex emotional and symbolic messages representing home as both psychological and social space. This study employs a qualitative approach using Roland Barthes’ semiotic analysis to explore denotative, connotative, and mythological meanings within visual narratives. The research object is a short movie released on YouTube in 2024, with data collected through visual observation and scene documentation. The analysis identifies visual signs and interprets them within contemporary cultural contexts. The findings reveal that home is constructed not merely as a physical space but as a symbol of relationships, emotional struggles, hope, and identity negotiation. The visual narrative constructs the myth of home as something collectively built rather than owned. This study contributes to visual communication and media semiotics within contemporary digital culture.